The breakdown of strength size scaling in spherical nanoindentation and microcompression of metallic glasses. (15th March 2017) - Wang, S.; Ye, Y.F.; Wang, Q.; Shi, S.Q.; Yang, Y.
Abstract: It was previously reported that the strength of metallic glasses (MGs) would scale inversely with the size of a sample or a deformation field, commonly known as "smaller-being-stronger". However, based on the extensive spherical nanoindentation experiments conducted across a variety of MGs, we demonstrate that such strength-size scaling breaks down at a critical indenter tip radius, which is caused by the transition of the yielding mechanism from bulk- to surface-controlled shear band initiation. Our experimental findings also provide an explanation for the unusual strength scattering observed in the micro-compression of MGs. Graphical abstract: